Automatic Guided Vehicle Systems in Flexible Manufacturing System –A review - Chawla, V. K.; Chanda, Dr A.K.; Chanda, Dr A.K.; Angra, Dr Surjit; Angra, Dr Surjit (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Material handling operations in flexible manufacturing systems has become efficient and easy with the improvement in automated machine technology. Material handling has been improved immensely since it started as fully manual operations, where men were employed to lift, stack and count the jobs in any manufacturing facility. Today’s rapid development in technology presents manufacturing firms a range of alternatives for in-plant transportation. Automated Guided Vehicle system (AGVs) are applied for advance material handling practices in a Flexible manufacturing facility consisting of a number of autonomous vehicles (AGVs) for movement of work part from one work center to another by following a particular guide path and their operations are controlled by a computer program. Now a day’s agent based AGV are also used in Material handling operations which operates and perform their assigned task autonomously. In this paper AGV system design and control in manufacturing facilities along with state of art review of the literature available on AGV guide path configurations, comparison of guide path configurations, estimation of the number of AGVs in a facility, scheduling and dispatching policies, routing, conflict resolution and positioning of AGVs has been reviewed and at the end of the paper, literature on Integrated policies for optimum utilization of AGVs is reported.